Recast layers on high speed steel surface after electrical discharge treatment in electrolyte - D. Krastev; V. Paunov; B. Yordanov (Fracture and Structural Integrity)
In this work are discussed some experimental data about the obtaining of recast layers on the surface of high speed tool steel after electrical discharge treatment in electrolyte. The electrical discharge treatment of steel surface in electrolyte produces a recast layer with specific combination of structure characteristics in result of nonequilibrium phase transformations. The modification goes by a high energy thermal process in electrical discharges on a very small area on the metallic surface involving melting, alloying and high speed cooling in the electrolyte. Obtained recast layers have a different structure in comparison with the metal matrix and are with higher hardness, wear- and corrosion resistance.